2021
DOI: 10.25040/ntsh2021.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Development of Periodontal Disease

Abstract: Introduction. Periodontal tissue disease is one of the most common dental pathologies, which among young people occurs with a frequency of 60% to 99%. Therefore, the problem of finding new links in the pathogenesis, the reasons for the growing prevalence of periodontal disease, as well as effective methods for its early diagnosis and prevention, is relevant. Objectives. Establish the possibility of using individual stomatological and psychophysiological features to predict the development of periodontal disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…In dental surgery, neural networks may be helpful in orthognathic surgery planning, prediction of post-extraction complications, bone lesion detection, and differentiation and implantological treatment planning [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Furthermore, artificial intelligence is spreading into periodontology and in the above-mentioned studies, it was used to evaluate the periodontal bone loss, peri-implant bone loss, and to predict the development of periodontitis due to the psychological features [ 49 , 50 , 51 , 52 , 53 , 54 ]. This review shows that artificial intelligence has developed very fast in recent years and it may become an ordinary tool in modern dentistry in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In dental surgery, neural networks may be helpful in orthognathic surgery planning, prediction of post-extraction complications, bone lesion detection, and differentiation and implantological treatment planning [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Furthermore, artificial intelligence is spreading into periodontology and in the above-mentioned studies, it was used to evaluate the periodontal bone loss, peri-implant bone loss, and to predict the development of periodontitis due to the psychological features [ 49 , 50 , 51 , 52 , 53 , 54 ]. This review shows that artificial intelligence has developed very fast in recent years and it may become an ordinary tool in modern dentistry in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that patients’ level of anxiety and stress hormone levels had an impact on periodontitis ( Table 5 ). Assessment of the condition of teeth hard tissues, the level of oral hygiene, and the evaluation of psychophysiological features with the use of neural networks can effectively predict the risk of periodontal disease development in young people [ 53 ].…”
Section: Neural Network In Periodontologymentioning
confidence: 99%
“…In the study of Jun-Young Cha et al, the bone loss percentage was calculated and classified by convolutional neural networks on periapical radiographs and its accuracy was 88.89%. This method can be used to assess the severity of peri-implantitis [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic sensitivity of the first prognostic model was 83.33% and the specificity was 92.31%. They concluded that assessment of the condition of teeth hard tissues, the level of oral hygiene, and the evaluation of psychophysiological features can effectively predict the risk of periodontal disease development in young people aged 18–23 [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Відомі дані про вплив типів погоди на розумову працездатність у старшокласників, які свідчать про її зниження із погіршенням погодних умов. Відомо, що за ІІІ типу погоди також погіршуються увага, пам'ять, розумові здібності, зростає латентний період складної зорово-моторної реакції [8,9].…”
unclassified